EFFECTIVITY OF INTERNAL AUDIT ON MANAGEMENT COMPLIANCE (A Case Study in "AJ Corporation") - Yustian, Yohanes Kevin (Jurnal Ilmiah Mahasiswa FEB, 2020)
Growing business nowadays needs to own well established internal control system so that they will enhance their performance to comply within the standard operational procedure. Emphasis on the asset security and the efficiency of the management compliance Internal Audit become one of the most exciting role to pursue in nowadays business circumstances. AJ Corporation are together of the mercantilism corporations whose viable marketed nationally in Indonesia. This study has the aim to grasp the implementation of the internal control management of financial cycle audit result divided into three parts of audit Petty Cash cycle Audit Result, Cash Cycle Audit Result and Physical Stock Cycle Audit Result in AJ corporation included the recommendations on weaknesses found within the control of management. Methodology the tactic the strategy employed in this analysis is qualitative descriptive method with case study approach. Data derived in this analysis obtained through observation and interview based on the Audit result that had been done for 12 months period. Fortunately, the result of the evaluation in AJ Corporation was done quite well with some minor problem indicated. However , The further Audit method and analysis in future are needed to cover the wider area of the business in order to enhance the management compliance of the whole business entity so the business internal control system could be more effective and internal audit program could also be more efficient. Keywords: Internal Control System, Internal Audit, Management Compliance